EFFECTS OF VARYING LEVELS OF SOAKED FALSE YAM (ICACINA OLIVIFORMIS) TUBER MEAL ON GROWTH PERFORMANCE AND SUBSEQUENT EGG-LAYING PERFORMANCE OF LAYER CHICKEN - Niayale, R.; Effah, K.; Dei, H.; Alhassan, M. (UDS International Journal of Development, 2023)
False yam (lcacina oliviformis) is a perennial shrub with large tuberous root, which is common in the arid and semi-arid areas of West and Central Africa. The tuber is rich in carbohydrates but contains some anti-nutritional factors like gum resins that can be partially removed by soaking in water. A feeding trial involving layer chicken was conducted to evaluate the effects of varying levels of sun-dried soaked false yam tuber meal on their performance during the grower phase and subsequent egg production phase. Harvested false yam tubers were peeled, chopped, soaked for 12 days in water, sun-dried for 6 days and milled into gritty flour and labeled Soaked False Yam Tuber Meal (SFYTM). The SFYTM was included in the diets of growing hens (pullets) at 0% (control), 5%, 7.5% and 10% as a substitute for maize on a weight-by-weight basis at the grower phase (9-19 weeks of age); after which all hens were fed a standard layer diet at the layer phase (20-29 weeks of age). A total of 120 Lohmann chicks brooded for 8 weeks with an average live weight of 525g per bird were randomly assigned to the 4 dietary treatments and each treatment was replicated thrice (n=10). Feed and water were given ad libitum. Data were analyzed by one-way ANOVA using GenStat. Only hens fed the 5% SFYTM diet at the grower phase had comparable performance to their control counterparts in terms of feed intake, live weight gain, feed conversion efficiency, egg weight and egg production. It is concluded that sun-dried soaked false yam tuber meal can be included at 5% in the grower diet of layer chicken with no adverse effects on growth and egg-laying performance. Keywords: False Yam, Growth Performance, Egg Production, Layer Chicken